Predictors of Longitudinal Trajectories of Alcohol Consumption in People with HIV. (29th January 2018) - Bilal, Usama; McCaul, Mary E.; Crane, Heidi M.; Mathews, W. Christopher; Mayer, Kenneth H.; Geng, Elvin; Napravnik, Sonia; Cropsey, Karen L.; Mugavero, Michael J.; Saag, Michael S.; Hutton, Heidi; Lau, Bryan; et al.
Abstract : Background: Our aim was to describe alcohol consumption trajectories in a cohort of people living with HIV and determine clinical and sociodemographic predictors of each trajectory. Methods: This is a prospective cohort study of 7, 906 patients in the 7 Centers for AIDS Research Network of Integrated Clinical Systems sites. Alcohol consumption was categorized as none, moderate, and alcohol misuse. Predictors included age, race/ethnicity, depressive or anxiety symptoms, illicit drug use (opioids, methamphetamines, cocaine/crack), marijuana use, hepatitis C virus (HCV) infection, HIV transmission risk factor, and HIV disease progression. We estimated sex‐stratified alcohol consumption trajectories and their predictors. Results: We found 7 trajectories of alcohol consumption in men: stable nondrinking and increased drinking (71% and 29% of initial nondrinking); stable moderate, reduced drinking, and increased alcohol misuse (59%, 21%, and 21% of initial moderate alcohol use); and stable alcohol misuse and reduced alcohol misuse (75% and 25% of initial alcohol misuse). Categories were similar in women, except lack of an increase to alcohol misuse trajectory among women that begin with moderate use. Older men and women were more likely to have stable nondrinking, while younger men were more likely to increase to or remain in alcohol misuse. Minorities, people with depressive or anxiety symptoms, HCV‐infected individuals, and people who injected drugs were more likely to reduce use. Illicit drug use was associated with a reduction in overall drinking, while marijuana use was associated with stable moderate drinking or misuse. Conclusions: Longitudinal trajectories of increasing alcohol use and stable misuse highlight the need to integrate routine screening and alcohol misuse interventions into HIV primary care. Abstract : Alcohol consumption trajectories are heterogeneous among People With HIV and range from people with stable use, who tend to have lower levels of other risk behaviors, to those whose consumption patterns vary, and have a higher prevalence of risk behaviors and other comorbidities. With the increased life expectancy of People With HIV, the potential for increased alcohol‐related morbidity and mortality has grown and highlights the need to integrate routine screening and interventions for alcohol misuse into HIV primary care.